Inhibition by Recombinant Hirudins of Experimental Venous Thrombosis and Disseminated Intravascular Coagulation Induced by Tissue Factor in Rats - Freund, Monique; Cazenave, Jean-Pierre; Courtney, Michael; Degryse, Eric; Roitsch, Carolyn; Bernat, André; Delebassée, Denis; Defreyn, Guy; Maffrand, Jean-Pierre (Thrombosis and Haemostasis, 1990)
Antithrombotic potency of recombinant hirudins rHV2, rHV2–Lys47 and rHV2–Arg47 was studied in a model of experimental thrombosis induced by tissue factor in the rat. Venous thrombosis was induced by i.v. injection of 25 mg/kg tissue factor followed by stasis of the inferior vena cava. In this model natural recombinant hirudins, rHV2 and rHV2–Lys47 injected 5 min before thromboplastin totally inhibited thrombosis in the same μg range as heparin or natural hirudin extracted from leeches. However, the mutant variant rHV2–Arg47 gave a maximal 60% inhibition of thrombosis. Variants rHV2–Lys47 (30 μg/kg) and rHV2–Arg47 (157 μg/kg) injected 5 min before thromboplastin prevented by 90 to 100% the drop in platelet count observed during the disseminated intravascular coagulation induced by thromboplastin injection. Recombinant hirudins were less anticoagulant than heparin as measured by an APTT on rat plasma. After rat tail transection, rHV2–Lys47 caused a 2–fold smaller prolongation of the bleeding time than an equivalent antithrombotic dose of heparin. Plasmatic elimination of rHV2–Lys47 from rat plasma after i.v. injection had a fast distribution phase with a half-life of 3 min during which 90% of injected rHV2–Lys47 was lost and was followed by a slower elimination phase. Thus recombinant hirudin rHV2–Lys47 appears as a promising potent antithrombotic agent for the prevention of thrombin-dependent venous thrombosis and disseminated intravascular coagulation